Genome-wide identification of a MADS-box transcription factor family and their expression during floral development in Coptis teeta wall - Shao-Feng Duan; Ji-Chen Yu; Timothy Charles Baldwin; Yuan Yuan; Gui-Sheng Xiang; Rui Cui; Yan Zhao; Xin-Chun Mo; Ying-Chun Lu; Yan-Li Liang (BMC Plant Biology)
Abstract Background MADS-box transcription factors have been shown to be involved in multiple developmental processes, including the regulation of floral organ formation and pollen maturation. However, the role of the MADS-box gene family in floral development of the alpine plant species Coptis teeta Wall, which is widely used in Traditional Chinese Medicine (TCM), is unknown. Results Sixty-six MADS-box genes were identified in the C. teeta genome. These genes were shown to be unevenly distributed throughout the genome of C. teeta. The majority of which (49) were classified as type I MADS-box genes and were further subdivided into four groups (Mα, Mβ, Mγ and Mδ). The remainder were identified as belonging to the type II MADS-box gene category. It was observed that four pairs of segmental and tandem duplication had occurred in the C. teeta MADS-box gene family, and that the ratios of Ka/Ks were less than 1, suggesting that these genes may have experienced purifying selection during evolution. Gene expression profiling analysis revealed that 38 MADS-box genes displayed differential expression patterns between the M and F floral phenotypes. Sixteen of these MADS-box genes were further verified by RT-qPCR. The 3D structure of each subfamily gene was predicted, further indicating that MADS-box genes of the same type possess structural similarities to the known template. Conclusions These data provide new insights into the molecular mechanism of dichogamy and herkogamy formation in C. teeta and establish a solid foundation for future studies of the MADS-box genes family in this medicinal plant species.